FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS SUNGAI ARE TAHUN 2024 - Arisah, Mila; Siti Aisyah; Eka Afrika; Fika Minata Wathan (JURNAL KESEHATAN INDRA HUSADA, 2025)
In Indonesia, the Maternal Mortality Rate (MMR) remains high. Hypertension during pregnancy frequently occurs and is one of the leading causes of maternal mortality. In Indonesia, hypertension in pregnancy ranks second as the leading cause of maternal death after hemorrhage. This study aims to examine the relationship between maternal factors and the incidence of hypertension in pregnant women in the working area of Sungai Are Public Health Center in 2024. The study employed an observational analytical design with a cross-sectional approach in Simpang Luas Village, Sungai Are District. The population consisted of 120 pregnant women in Sungai Are Public Health Center. Using purposive sampling techniques, a total sample of 30 was obtained. Data analysis included univariate distribution and bivariate analysis using the ChiSquare test with a significance level of 5% (a = 0.05). The results showed significant relationships between age (p = 0.000), obesity (p = 0.013), history of hypertension (p = 0.000), and the incidence of hypertension among pregnant women in the working area of Sungai Are Public Health Center in 2024.